Factors Influencing Occupational Health Issues Of Contract Workers In Construction Industry In Tamilnadu: Construction - K. Kanagaraj; Dr. M. Devanathan (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Construction industry is one of the biggest industries in India and it has provided employment opportunities to more than 50 million people in the country. Workers working in the construction industry are handling many types of raw materials and they are living in the polluted working environment. Hence there are many factors that affect the health of contract workers in the construction industry. The study attempted to analyse the factors influenced the health of contract workers in the construction industry in the state of Tamilnadu with the sample size of 385 contract workers working in various construction companies in the districts of Cuddalore, Vellore, Thoothukudi, Erode and tiruchirappalli. The study evidenced that majority of the respondents (52.7%) were below 40 years of age. Majority of the respondents (63.9%) had a work experience of more than 10 years in construction industry, majority of the respondents (58.4%) were labours and majority of the contract workers in construction industry were working more than the normal working hours (8 hours). Material and equipment used in the construction industry was found to be the most severe factor that influenced on the contract workers’ health and ‘lack of safety measures’ was found to be the least severe factor. Age, nature of work and working hours of the contract workers had significant relationship with the factor of ‘work related factors’. Awareness level, age and nature of work had significant relationship with the factor of ‘material and equipment’. Awareness level, experience in construction work and nature of work had significant relationship with the factor of ‘work environment. Awareness level, age and experience of contract workers had significant relationship with the factor of ‘lack of safety measures’ and nature of work and working hours had significant relationship with psychological factors.